Novel EGFP reporter cell and mouse models for sensitive imaging and quantification of exon skipping - Hara, Y; Mizobe, Y; Inoue, YU; Hashimoto, Y; Motohashi, N; Masaki, Y; Seio, K; Takeda, S; Nagata, T; Wood, MJA; Inoue, T; Aoki, Y (Nature Research, 2020)
Duchenne muscular dystrophy (DMD) is a fatal X-linked disorder caused by nonsense or frameshift mutations in the DMD gene. Among various treatments available for DMD, antisense oligonucleotides (ASOs) mediated exon skipping is a promising therapeutic approach. For successful treatments, however, it is requisite to rigorously optimise oligonucleotide chemistries as well as chemical modifications of ASOs. To achieve this, here, we aim to develop a novel enhanced green fluorescence protein (EGFP)-based reporter assay system that allows us to perform efficient and high-throughput screenings for ASOs. We design a new expression vector with a CAG promoter to detect the EGFP fluorescence only when skipping of mdx-type exon 23 is induced by ASOs. Then, an accurate screening was successfully conducted in C57BL/6 primary myotubes using phosphorodiamidate morpholino oligomer or locked nucleic acids (LNA)/2′-OMe mixmers with different extent of LNA inclusion. We accordingly generated a novel transgenic mouse model with this EGFP expression vector (EGFP-mdx23 Tg). Finally, we confirmed that the EGFP-mdx23 Tg provided a highly sensitive platform to check the effectiveness as well as the biodistribution of ASOs for exon skipping therapy. Thus, the assay system provides a simple yet highly sensitive platform to optimise oligonucleotide chemistries as well as chemical modifications of ASOs.